2015
DOI: 10.1515/dcse-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

UN Global Action Programme and Education for Sustainable Development: A Critical Appraisal of the Evidence Base

Abstract: The United Nations (UN) proclaimed the years 2005 to 2014 the World Decade on Education for Sustainable Development (ESD). As a follow up on the World Decade, the UN launched a Global Action Programme (GAP) that is designed to set the framework for international activities on ESD. The GAP focuses on five priority areas that are of high relevance for further implementation of ESD in educational systems.The research presented in this paper results from a training research course that was conducted with advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…The UN Global Action Plan for Sustainable Development (Fischer et al . ) has recognised students as important potential change agents within their professions. Fischer et al .…”
Section: Nutrition Professionals and Sustainabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The UN Global Action Plan for Sustainable Development (Fischer et al . ) has recognised students as important potential change agents within their professions. Fischer et al .…”
Section: Nutrition Professionals and Sustainabilitymentioning
confidence: 99%
“…Fischer et al . () recommend that sustainability practices should be integrated into education through whole institution approaches, with students as active participants in the process. A major challenge is to embed this emerging topic throughout the nutrition profession curricula.…”
Section: Nutrition Professionals and Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Grounded in a socio-cultural view of learning and a critical approach to education, the use of participatory methods requires re-conceptualizing science knowledge, science practitioners, and science education, as well as moving from a focus on individual possession of knowledge toward public, distributed knowledge embedded in particular places and in matters of local concern (Fisher, et al, 2015). Thus, learning science becomes an avenue for social action that emerges in terms of a particular issue and represents both personal and collective interests (Brunold, 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In fact, several studies have shown that supportive teacher-student relationships make students more satisfied with school experience and create a feeling of security in the classroom environment (Baker, Grant, & Morlock, 2008;Fischer, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%